2014
DOI: 10.1007/s10640-014-9847-z
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for the Effects of Information in a Public Goods Discrete Choice Model

Abstract: This paper develops a reduced form method of controlling for differences in information sets of subjects in public good discrete choice models, using stated preference data. The main contribution of our method comes from accounting for the effect of information provided during a survey on the mean and the variance of individual-specific scale parameters. In this way we incorporate both scale heterogeneity as well as observed and unobserved preference heterogeneity to investigate differences across and within i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 62 publications
0
38
1
Order By: Relevance
“…Another route to specify cut-off points is to look at confidence intervals of WTP estimates. Variance of estimated WTP is driven by the relative magnitude of the random term of utility, which in turn is determined by scale (Czajkowski et al 2014a). If for some (groups of) respondents scale is found to be so low that resulting confidence intervals of WTP estimates are too large to be meaningful, these responses could be discarded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another route to specify cut-off points is to look at confidence intervals of WTP estimates. Variance of estimated WTP is driven by the relative magnitude of the random term of utility, which in turn is determined by scale (Czajkowski et al 2014a). If for some (groups of) respondents scale is found to be so low that resulting confidence intervals of WTP estimates are too large to be meaningful, these responses could be discarded.…”
Section: Discussionmentioning
confidence: 99%
“…Response time is likely to be just one of such systematic influences on choice randomness. Familiarity of with the good to be valued (Czajkowski et al 2015), level of education (Czajkowski et al 2014b) or choice certainty (Beck et al 2013) have been shown to be other potential factors. Beyond that, other variables evaluating the choice task from the perspective of the respondent, such as attribute attendance, protest attitudes or previous experience as a survey participant should be accounted for in such a model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it should be noted that today there is no universal tool of controlling. It is believed that benchmarking, potential analysis, SWOT analysis, moderation method, analysis of strategic deviations, system of balanced parameters, strategy maps, system of distribution of indirect costs, standard quality, Six Sigma, policy of open reporting, theory of constraints, scenario development, system of accounting and cost analysis are the tools of strategic controlling which are most adapted to the use at industrial enterprises in modern conditions [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%